Tinjauan Yuridis Terhadap Pembatalan Perjanjian Sewa Menyewa Tanah Antara Perusahaan Umum Kereta Api Dan P.T. Basko Minang Plaza Dalam Perkara Perdata Putusan Nomor : 12/Pdt.G/2012/Pn/Pdg Di Kota Padang - Fenandri, Nathasya Nadia; Hanifah, Mardalena; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Cancellation of the agreement is the return everything to its original state, such as when the agreement was first held. Cancellation of the agreement can be done by absolute cancellation (relatief nietigheid), the cancellation must be requested by either party. Meaning more leads to the cancellation of the contract formation process or agreement (conclusion of the contract or agreement). Result in the cancellation of the contract is the law of return to its original position, as well as before the conclusion ofthe contract.The purpose of this study was to determine the reasons cancellation of the agreement in civil Nomor.12 / PDT.G / 2012 / PN.PDG and to determine the consideration of the judges who made the basis for examining and deciding the case Nomor.12 / PDT.G / 2012 / PN.PDG. Research by the author is classified into types of normative legal research done by researching library materials or secondary data. Based on the descriptive nature is to collect data in accordance with the truth then the data is compiled and processed and analyzed to provide a systematic overview of the facts and characteristics of the object and the subject under study accurately.The lawsuit cancellation agreement based on a civil case No. 12 / Pdt.G / 2012 / PN.PDG filed by the plaintiff against the defendant begins with the land lease agreement between the plaintiff and the defendant, during which the lease is the defendant does not pay the rent of land to plaintiffs started from 2004 until 2012. The plaintiff had to tell the defendant to pay the rent of the land but of pihat defendant no response or reply. Based on the above, with the fulfillment of the elements of cancellation of the agreement in Article 1266 of the Civil Code, the author believes that the judge had correctly applied the law, the cancellation of the agreement dilakukakan by PT. Train and PT. Basko Minang Plaza does have the right to be sued by the act of default.Keywords: Agreement-Cancellation of Agreement -Lease Agreement